2007
DOI: 10.21273/hortsci.42.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ploidy Level and Its Effects on Guard Cell Length, Pollen Diameter, and Fertility in Hydrangea macrophylla

Abstract: Ploidy level was estimated in Hydrangea macrophylla (Thunb) Ser. using flow cytometry. For H. macrophylla ssp. macrophylla, 42 diploid and 19 triploid cultivars were identified. All 14 H. macrophylla ssp. serrata (Thunb.) Makino cultivars tested were diploids. Somatic chromosome counts confirmed the ploidy of three diploid (2n = 2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 10 publications
6
39
0
1
Order By: Relevance
“…genome size estimates presented herein likely slightly overestimate the total nuclear DNA content of the H. macrophylla we tested (Zonneveld, 2004;Jones et al, 2007). The number of offspring that produced flowers ranged from 0% for 3x × 3x crosses to 73% for 2x × 2x crosses ( Table 5).…”
Section: Genome Size and Pollen Viability Of Seedlingsmentioning
confidence: 86%
See 4 more Smart Citations
“…genome size estimates presented herein likely slightly overestimate the total nuclear DNA content of the H. macrophylla we tested (Zonneveld, 2004;Jones et al, 2007). The number of offspring that produced flowers ranged from 0% for 3x × 3x crosses to 73% for 2x × 2x crosses ( Table 5).…”
Section: Genome Size and Pollen Viability Of Seedlingsmentioning
confidence: 86%
“…In interploidy hybridizations, the parental genome contributions are altered, which affects endosperm development and the formation of viable seeds (Schatlowski and Köhler, 2012). Jones et al (2007) reported that mean number of seed per cross and percent seed germination were higher when triploid cultivars were used as the pistillate (female) rather than the staminate (male) parent in controlled crosses. Results herein indicated that not only does parental ploidy influence seed set and seed germination, but that parental influence continues throughout plant growth and flowering.…”
Section: Seed Set Germination and Seedling Growthmentioning
confidence: 99%
See 3 more Smart Citations